2006
DOI: 10.4049/jimmunol.176.5.2864
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenicity and Immunomodulatory Function of Osteogenic Cells Differentiated from Mesenchymal Stem Cells

Abstract: Multipotent mesenchymal stem cells (MSC) are reported to be immunoprivileged as well as immunosuppressive. Hence, they are ideal candidates for allogeneic transplantation to induce regeneration of diseased tissues and organs. However, it is not known whether MSC would retain their immunoprivileged and immunomodulatory properties after differentiating into the local cell types of the transplantation site. This study sought to investigate this question with a novel New Zealand White rabbit osteogenesis model. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
165
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 51 publications
9
165
1
4
Order By: Relevance
“…These studies have yielded variable results and no consensus conclusion has been reached. Some studies have shown that soluble factors such as TGFb [22] and PGE2 [6] mediate the immunosuppressive effect of MSCs [27][28][29]; while other researchers have argued that direct cell-cell contact is the major mechanism [30][31][32]. In the present study, we generated MSC clones from mouse bone marrow and verified that the majority of these clones possessed differentiation potential.…”
Section: Introductionmentioning
confidence: 57%
“…These studies have yielded variable results and no consensus conclusion has been reached. Some studies have shown that soluble factors such as TGFb [22] and PGE2 [6] mediate the immunosuppressive effect of MSCs [27][28][29]; while other researchers have argued that direct cell-cell contact is the major mechanism [30][31][32]. In the present study, we generated MSC clones from mouse bone marrow and verified that the majority of these clones possessed differentiation potential.…”
Section: Introductionmentioning
confidence: 57%
“…For cells of the endothelial differentiation lineage, it was shown that CIITA-induced MHC class II expression is able to trigger proliferation of CD4(+) T cells independent of other T-cell costimulatory ligands [29]. The importance of the inducible MHC class II expression for the immunogenicity of allogeneic adult mesenchymal stem cells (MSC) and their osteogeneic derivatives was discussed by Liu et al [30]. In that study the differentiated MSC were also not able to express MHC class II after IFNγ stimulation in vitro, but expression gradually occurred at later time points after transplantation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent studies confirmed immunological properties of bone cells [19][20][21][22]24], direct chemotactic and immunomodulatory effects of OBL and OCL have not been precisely determined. In the co-culture model we demonstrated both the ability of lymphocytes to affect bone cell differentiation and their chemotactic properties, and of bone cells to modulate the cytokine and activation profile of lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation of human OBLs expresses the major histocompatibility complex class II (MHC-II) and costimulatory molecules, thus participating in antigen presentation and T lymphocyte activation [17]. On the other hand, OBL lineage cells as well as their ancestry, bone-marrow derived mesenchymal stem cells (MSC) may exhibit immunosuppressive properties by secreting immunosuppressive cytokines and stimulating regulatory T lymphocytes [20][21][22]. It has been recently proposed that MSC may be polarized toward either the proinflammatory or the immunosuppressive subpopulation depending on the toll like receptor (TLR) triggered by an exogenous danger signals [23].…”
Section: Introductionmentioning
confidence: 99%